Chemical Composition and Bioactive Properties of Stevia rebaudiana leaves Planted in Syria (Damascus University Journal of agriculture sciences, 2023)
This study was done in the laboratories of Food Science Department- College of Agriculture - Damascus University and Biotechnology - Ministry of Higher Education during 2020- 2021. The aim of this research was to determine the chemical composition, stevioside glycoside and bioactive compounds of dried Stevia rebaudiana leaves which planted at the Faculty of Agriculture - Damascus University. The results showed that the moisture, protein, ash and fat content of dried leaves were 10.11%, 11.81%, 14.55% and 4.54% respectively. The total carbohydrate content was the main components (52.61%), and the percentage of total soluble sugars, reducing sugars, non-reducing sugars and crude fiber were 16.35%, 5.44%, 10.91% and 16.5% respectively. The total energy of dried leaves was 298.54 kcal/100g. For the Functional biochemical components, Stevioside glycoside content was 6.08%, total phenolic compounds were 3275 mg gallic acid equivalent /100 g, and free radicals scavenging activity according to the colorimetric method (DPPH) was (86.97%). The pH of aqueous extract was 5.5% and TSS was 3.7%.
Keywords: Stevia rebaudiana; Stevioside glycoside; Chemical Composition; Bioactive properties